Effector proteins of rust fungi - Petre, Benjamin; Joly, David L.; Duplessis, Sébastien (Frontiers in Plant Science, 2014)
Rust fungi include many species that are devastating crop pathogens. To develop resistant plants, a better understanding of rust virulence factors, or effector proteins, is needed. Thus far, only six rust effector proteins have been described: AvrP123, AvrP4, AvrL567, AvrM, RTP1, and PGTAUSPE-10-1. Although some are well established model proteins used to investigate mechanisms of immune receptor activation (avirulence activities) or entry into plant cells, how they work inside host tissues to promote fungal growth remains unknown. The genome sequences of four rust fungi (two Melampsoraceae and two Pucciniaceae) have been analyzed so far. Genome-wide analyses of these species, as well as transcriptomics performed on a broader range of rust fungi, revealed hundreds of small secreted proteins considered as rust candidate secreted effector proteins (CSEPs). The rust community now needs high-throughput approaches (effectoromics) to accelerate effector discovery/characterization and to better understand how they function in planta. However, this task is challenging due to the non-amenability of rust pathosystems (obligate biotrophs infecting crop plants) to traditional molecular genetic approaches mainly due to difficulties in culturing these species in vitro. The use of heterologous approaches should be promoted in the future.